The impact of ICT sourcing on ICT organisation, competences and continuous innovation. (1st January 2012) - Balocco, Raffaello; Ciappini, Alessia; Corso, Mariano
This paper aims to provide a description of how different information and communication technology (ICT) sourcing strategies can impact on the organisational characteristics of the ICT department, its competences and on its continuous innovation. ICT sourcing can be a strategic lever to guarantee effectiveness and, at the same time, to increase an enterprise's dynamic capabilities and foster continuous innovation. Innovation and learning can be enabled by collaboration with a network of specialised and integrated suppliers of ICT services and technologies. The work is based on a survey of 79 enterprises and an empirical study involving 40 cases. Evidence derived from the sample supports the identification of suitable sourcing models, coherent in terms of strategy, organisation and competence management, in order to manage suppliers as a potential source of innovation. Research results also pinpoint the barriers keeping ICT suppliers from carrying out their role as true innovators in an enterprise's continuous innovation process.